Preliminary X-ray crystallographic studies of a Lys49-phospholipase A(2) homologue from Bothrops pirajai venom complexed with p-bromophenacyl bromide and alpha-tocopherol inhibitors - Santos, Juliana I. dos [UNESP]; Marchi-Salvador, Daniela P. [UNESP]; Fernandes, Carlos A. H. [UNESP]; Silveira, Lucas B.; Soares, Andreimar M.; Fontes, Marcos R. M. [UNESP] (Bentham Science Publ Ltd, 2007)
PrTX-I, a non-catalytic and myotoxic Lys49-PLA(2) from Bothrops pirajai venom has been crystallized alone and in complex with bromophenacyl bromide (BPB), alpha-tocopherol and alpha-tocopherol acetate inhibitors. These crystals have shown to diffract X-rays between 2.34 and 1.65 angstrom resolution. All complexes crystals are isomorphous and belong to the space group P2(1) whereas native PrTX-I crystals belong to the P3(1)21.
Keywords: α-tocopherol; Bothrops pirajai venom; Crystallization; Lys49-phospholipase A2; Myotoxity; p-BPB; P-bromophenacyl bromide; Vitamin E; X-ray crystallography; Alpha tocopherol; Bromide; Enzyme inhibitor; Lysine; Phospholipase A; Snake venom; Animal; Chemical structure; Chemistry; Protein conformation; Snake; X ray crystallography; Alpha-Tocopherol; Animals; Bothrops; Bromides; Crotalid Venoms; Crystallography, X-Ray; Enzyme Inhibitors; Lysine; Models, Molecular; Phospholipases A; Protein Conformation; Bothrops pirajai